Brigadas Médicas Cubanas “Henry Reeve” en el enfrentamiento a la COVID-19 / Cuban Medical Brigades “Henry Reeve” in the confrontation with COVID-19 - Barnés Domínguez, José (Panorama. Cuba y Salud, 2020)
El Ccontingente Internacional de Médicos Especializados en Situaciones de Desastres y Graves Epidemias Henry Reeve, fue creado por nuestro Comandante en Jefe Fidel Castro, en septiembre de 2005 para asistir a los damnificados por el huracán Katrina, en Estados Unidos, misión inconclusa ante la negativa del gobierno de ese país para recibir esa ayuda. ABSTRACT The International Contingent of Doctors Specialized in Situations of Disasters and Serious Epidemics Henry Reeve, was created by our Commander in Chief Fidel Castro, in September 2005 to assist those affected by Hurricane Katrina, in the United States, an unfinished mission due to the refusal of the government of that country to receive that aid.